ICNITES DE TETRAPODOS PERMICOS DEL SUR DE MENDOZA (Ameghiniana, 2013)
Tetrapods footprints discovered in Sierra Pintada (near San Rafael, Mendoza province, Argentine) are described. Footprints have been found in cross-bedded sandstones of Los Reyunos formation (Cochicó Group) and they are of Permian age. Taxonomic ubication into Stereospondyli Labirinthodontia (at the present unknown in the Argentine Permian) of the footprints, is suggested.